Oral vaccination of Macrobrachium rosenbergii with baculovirus-expressed M. rosenbergii nodavirus (MrNV) capsid protein induces protective immunity against MrNV challenge. Issue 86 (March 2019) - Citarasu, Thavasimuthu; Lelin, Chinnadurai; Babu, Mariavincent Michael; Anand, Setty Balakrishnan; Nathan, Abel Arul; Vakharia, Vikram N.
Abstract: White Tail Disease (WTD) is one of the important viral diseases of fresh water giant prawn Macrobrachium rosenbergii, which is caused by Macrobrachium rosenbergii nodavirus ( Mr NV). In the present study, the capsid protein gene of Mr NV containing a His-tag was cloned into a baculovirus vector pVL1393 and expressed the recombinant Mr NV protein in insect cells, using a baculovirus expression system. A band corresponding to the Mr NV protein of 43 kDa was characterized after fractionating the proteins of baculovirus-infected cell lysates by SDS-polyacrylamide gel, and immunostaining with His-tag monoclonal antibody. Furthermore, purified Mr NV capsid protein assembled into virus-like particles (VLPs) of ∼30 nm in diameter, when examined by transmission electron microscopy (TEM). To vaccinate the larvae by oral route, the recombinant Mr NV (r- Mr NV) protein was coated with artificial prawn feed and fed to M. rosenbergii larvae (90 ± 10 mg) for 60 days. After 30 and 60 days of vaccine treatment, group of prawns were challenged with virulent Mr NV orally. Samples were collected at different time intervals to evaluate the survival of larvae and to analyze the presence of Mr NV by double-step PCR and expression of immune/ toll-like receptor (TLR) genes. Non-vaccinated group of M. rosenbergii larvae succumbed to death and had 90% mortality, whereas the r- Mr NV protein treated groups exhibited 65 and 80% survival (P  ≤  0.001) for 30 and 60 days post-vaccination (dpv), respectively. Double-step PCR diagnosis revealed that there was 100% positive signals observed in non-vaccinated prawn group, whereas the infection was reduced significantly (P < 0.001) to 32 and 17% respectively in 30 and 60 dpv. Among the four different immune/ TLR genes such as antimicrobial peptide ( Mr amp), lysozyme ( Mr LY), proPhenol Oxidase ( Mr PPO) and Toll-Like Receptor ( Mr Toll) expression screening, Mr amp was successfully expressed in the Mr NV subunit protein vaccinated prawns, whereas the non-vaccinated prawn had no immune/TLR gene expression. Taken together, our results demonstrate that oral vaccination of M. rosenbergii larvae with baculovirus-expressed Mr NV capsid protein confer up to 78% protection against Mr NV infection. Graphical abstract: Image 1 Highlights: Mr NV CP gene was cloned to baculovirus expression vector and expressed the protein. Mr NV CP and Virus Like Particle expressed through baculovirus expression system. Purified r Mr NV CP was fed to Macrobrachium rosenbergii and studied the survival and immunity. r Mr NV CP treated M. rosenbergii had improved survival and immunity.